2012
DOI: 10.1158/1055-9965.epi-11-1140
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Merkel Cell Polyomavirus Associated with Incident Lymphoma in the Epilymph Case–Control Study in Spain

Abstract: Background: Merkel cell polyomavirus (MCV) has been identified as the cause of Merkel cell carcinoma. The increased incidence of chronic lymphocytic leukemia in Merkel cell cancer cohorts and the lymphotropic properties of the virus suggest a possible viral association with lymphomagenesis. To investigate this potential role, we explored seroreactivity against MCV VP1 capsids within the Epilymph case-control study in Spain.Methods: Serum samples from 468 incident lymphomas, categorized into up to 11 entities, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
10
2
Order By: Relevance
“…Differences from our previous results in MCPyV seroprevalence (Robles et al, 2012), in which we observed an increased seroprevalence, might be explained by control selection, due to the previous use of hospital controls versus the current use of general population ones. The decreased seroprevalences against all polyomaviruses in our CLL subjects is somehow consistent with the findings from Teras et al (2014), in which none of the polyomaviruses showed a significant association with CLL, but half of them showed a decreased risk of CLL among seroprevalent subjects.…”
Section: Received 9 January 2015contrasting
confidence: 99%
See 1 more Smart Citation
“…Differences from our previous results in MCPyV seroprevalence (Robles et al, 2012), in which we observed an increased seroprevalence, might be explained by control selection, due to the previous use of hospital controls versus the current use of general population ones. The decreased seroprevalences against all polyomaviruses in our CLL subjects is somehow consistent with the findings from Teras et al (2014), in which none of the polyomaviruses showed a significant association with CLL, but half of them showed a decreased risk of CLL among seroprevalent subjects.…”
Section: Received 9 January 2015contrasting
confidence: 99%
“…However, the presence of a truncated LT-Ag MCPyV sequence in the nucleus, a peculiarity of MCPyV in Merkel cell carcinoma cells, has been reported in highly purified CD19 + /CD5 + CLL cells (Haugg et al, 2011;Pantulu et al, 2010). Serology data are furthermore inconsistent; in a previous case-control study we identified an increased MCPyV seroprevalence in CLL patients (Robles et al, 2012) whereas in a recent paper a decreased risk was observed (Teras et al, 2015), although none of them significant. The latter paper also observed null associations for seven additional polyomaviruses and subsequent risk of CLL, although potential concerns in sample size were raised.…”
Section: Received 9 January 2015mentioning
confidence: 65%
“…Finally, the high seroreactivity could also be related to a viral reactivation in temporal proximity to cancer development; the latter happening before and maybe contributing to bladder cancer pathogenesis or happening later as a result of an immune system impairment after the disease onset. The higher seroreactivity observed for not only one but two viruses, as well as our previous observation of a higher seroprevalence in lymphomas, could indicate reverse causality (high seroreactivity as a consequence of immune impairment) rather than a causative role. However, other viruses such as EBV or HPV are able to cause more than one cancer depending on the body location and geographic area.…”
Section: Discussionmentioning
confidence: 51%
“…A recent International Agency for Research on Cancer panel classified Merkel cell polyomavirus (MCV) as a probable carcinogen and BK and JC polyomaviruses (BKV, JCV) as possible carcinogens (1). In the only three epidemiologic studies (2)(3)(4) to examine associations of BKV and JCV antibodies with risk of non-Hodgkin lymphoma (NHL) or NHL subtypes, no associations were found for BKV, but for JCV results were inconsistent. The only study to examine MCV and risk of NHL showed positive associations with some NHL subtypes (4).…”
Section: Introductionmentioning
confidence: 99%
“…In the only three epidemiologic studies (2)(3)(4) to examine associations of BKV and JCV antibodies with risk of non-Hodgkin lymphoma (NHL) or NHL subtypes, no associations were found for BKV, but for JCV results were inconsistent. The only study to examine MCV and risk of NHL showed positive associations with some NHL subtypes (4). Because of the limited number of studies to date, we examined associations of plasma antibody levels of JCV, BKV, and MCV-as well as several other polyomaviruses [WU polyomavirus (WUV); KI polyomavirus (KIV); human polyomavirus 6 (HPy6); human polyomavirus 7 (HPy7); Trichodysplasia spinulosa-associated polyomavirus (TSV)]-with risk of NHL in the American Cancer Society (ACS) Cancer Prevention Study-II (CPS-II) Nutrition Cohort, a large prospective study of U.S. men and women.…”
Section: Introductionmentioning
confidence: 99%